Comparison of demographic factors and selected maternity care variables in women who chose midwife-led or obstetrician-led antenatal care respectively - Łata, Aleksandra; Baranowska, Barbara; Węgrzyn, Piotr (Nursing in the 21st Century, 2019)
COMPARISON OF DEMOGRAPHIC FACTORS AND SELECTED MATERNITY CARE VARIABLES IN WOMEN WHO CHOSE MIDWIFE-LED OR OBSTETRICIAN-LED ANTENATAL CARE RESPECTIVELY Introduction. The midwife profession is an independent profession, entitled to provide part of the services of gynaecology and obstetrics. Women whose pregnancy goes in a physiological way may benefit from midwife-led services as part of the benefits refunded by the National Health Fund. This model makes it possible to maintain continuity of care, considered a beneficial solution in the area of mother and child health. Aim. Determination of the scale of the phenomenon of midwife-led antenatal care in Poland and comparison of groups of women actively using the Internet who chose midwife-led or doctor-led antenatal care. Material and methods. The survey was carried out in February-March 2018. The research tool was an electronic questionnaire. Questions regarding socio-demographic factors of pregnancy, antenatal education, labour, intervention during labour and labour experience described by women-Internet users were used for the purpose of the analysis. The Chi-square test of independence, the Fisher’s Exact Test and the Mann-Whitney U test were used to develop the results. Results and conclusions. The prenatal care of midwives is not a common phenomenon in Poland. Groups of women who decide on a different form of midwife-led or doctor-led antenatal care differ mainly in the material situation. Women choosing midwifeled antenatal care more often attend antenatal classes and prepare a birth plan. In order to popularize the model of antenatal care provided by midwives, attempts should be made to study the motivation of women who decide on an alternative antenatal care.